Letramento literário e escolarização - limites e possibilidades - Oliveira, Antonia Sergiana Tavares de (2020)
This study aims at analyzing the schooling processes of literary reading and their possibilities of assuring or guaranteeing an expansion of the conditions that define Literary Literacy. To attain such an objective, we investigated Literary Literacies practices in Literature classes and in events promoted by Projeto Mergulhando na Leitura e na Escrita, developed by Estado da Bahia School, located in Crato, Ceará. The theory and method of our study is based on the sociocultural Literacy approach conceived from the New Literacy Studies - NLS (New Literacy Studies), as proposed by Brian Street (1984, 1993, 2006, 2014), Scribner and Cole (1981), Heath (1983) and Barton, Hamilton and Ivanic (2000). In this perspective, and considering the Brazilian context, we can mention as relevant studies the ones conducted by Soares (2014a), Rojo (2000, 2006) and Kleiman (2012). The Literary Literacy was approached from Cosson´s theoretical perspective (2011, 2009, 2014); Paulino (1997, 2000, 2001, 2004, 2005, 2014); Zilberman (1982, 1990, 2005) and Soares (2003, 2009 e 2014b). The conception of Literature used is based on the studies that conceive the literary phenomenon as a social fact (LEAHY-DIOS, 2000; CÂNDIDO, 2011). Considering the sociocultural nature of literacy and the objectives we propose, this research is descriptive, implemented with a qualitative perspective, with an ethnographic approach. As research techniques for data collection, we used participant observation. The analysis carried out considered the theories that supported this study, the establishment of categories and the methodological assumptions that hold this research. The results indicate that the relation between schooling and Literary Literacy shows meeting points which demonstrate that, even in the school space, there is the possibility of working literary reading proficiently, taking into account the reading protocols adopted in extracurricular activities and thus, expanding the paths that guarantee Literary Literacy.